Application of the monitoring module in the educational process of universities - Antonov, A.V.; Prokhorenko, A.O.; Dmitrieva, N.G. (Theory and Practice of Physical Culture, 2026)
Objective of the study is substantiation and implementation of the module for monitoring the level of physical fitness of university students in the educational process. Methods and structure of the study. Within the framework of this study, a comprehensive methodological toolkit was used to achieve the set goals, including a review of specialized literature and legal acts, a questionnaire survey, and analytical modeling. The study was conducted in two consecutive stages. In the first stage, a detailed analysis of the use of digital technologies in educational activities by leading universities in St. Petersburg was conducted. In the second stage, the need for the development and implementation of a module for monitoring students' physical fitness was identified, and a methodological framework for its operation was developed. Results and conclusions. The implementation of a module for monitoring the physical fitness level of university students is an innovative approach to optimizing the physical education process. This module, integrated into the educational program system, aims to enhance the effectiveness of physical training and transition from traditional normative methods to individualized, person-centered strategies, which not only improves the physical condition of students but also fosters a conscious attitude towards a healthy lifestyle.